Apni Boli-Script Book in Malayalam Level-1 - Syamala Kumari, B.; Solaman, R. (Central Institute of Indian Languages Mysore, 1973)
The book is a primer for learning Malayalam script.
Keywords: Malayalam; Language Learning; Malayalam